Media Edukasi Kartu Bergambar untuk Memilah Sampah pada Siswa PAUD Srikandi - Mahdalena, Vina; Handayani, Lusia; Uljanatunnisa, Uljanatunnisa (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Environmental communication has shifted to the concept of Sustainable Development Goals (SDGs) or Sustainability Communication. Data from the Ministry of Environment and Forestry (KLHK) in 2019, Indonesia produces at least 64 million tons of waste piles every year. Based on this data, about 60% of the waste is transported and dumped to the final dump, 10% of the waste is recycled, and the remaining 30% is not managed. In fact, the government has a target in 2025 that waste must be managed 100%. The solution that we can provide as academics in the field of Communication Science is to help teacher to educate their students what is meant by "Throwing garbage in its place". We will design educational media for children as the output of this activity in the form of flashcards that can be used by schools to educate students in sorting organic, non-organic and B3 waste (hazardous and toxic materials). This card is played in groups so that students' knowledge can be measured. The interaction that is built is also quite good between the teacher and students because all children can be controlled in small groups (containing 4-5 people) and have their turn to play cards. The results of the activity proved to be able to increase students' knowledge because the final test results obtained an average of 69.18. So, flash cards effective as an educational medium for sorting waste for ECED students.